Challenges and Strategies in School Improvement: School Principals' Experiences and Reflections - Dinler, Caner (International Journal of Asian Education, 2024)
This study examines the experiences of public primary school principals in Istanbul in implementing school improvement strategies, addressing challenges, and assessing the outcomes of their efforts. Using a qualitative case study design, data were collected through semi-structured interviews with nine experienced principals, focusing on their activities, challenges, and solutions in fostering educational change. The findings highlight the importance of systematic planning, creating supportive learning environments, and fostering participatory leadership to drive school improvement. Collaborative approaches, involving teachers, parents, and community stakeholders, were emphasized as key to achieving shared goals. Principals faced several challenges, including a lack of organizational culture, resistance to change, excessive administrative demands, inadequate physical conditions, and resource limitations. To address these issues, they employed strategies such as building participatory school cultures, establishing effective communication networks, and leveraging external support from NGOs and municipalities. These efforts not only mitigated immediate barriers but also strengthened stakeholder relationships and promoted a sense of collective ownership. The results indicate significant positive impacts on students, teachers, and parents. School improvement initiatives enhanced student engagement, increased teacher satisfaction, and improved school-community relationships. Principals also reported that their schools became more desirable within their communities, reflecting the broader benefits of their leadership efforts. This study contributes to understanding effective school improvement practices in urban settings and underscores the importance of systemic support and equitable resource allocation. It provides actionable insights for policymakers and educators, emphasizing the need for sustainable strategies to ensure continuous progress in education.